The influence of current ratio, debt to equity ratio, earnings per share, and net profit margin on the stock prices of mining companies in the oil, gas, and coal sub-sector - Wijayanti, Maharani Rahma; Zulfikar, Zulfikar (Junal Ilmu Manajemen, 2024)
This study analyzes the influence of current ratio, debt to equity ratio, earnings per share, and net profit margin on stock prices, which is the aim of this research. The sample selection method used purposive sampling technique from annual reports and financial statements of each company in the coal, oil, and gas mining sub-sectors listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. The total initial sample size was 81 for the period 2020-2022. After testing, 18 samples were identified as outliers and excluded, leaving 63 samples for data analysis. The data analysis technique employed was multiple linear regression using SPSS version 26. The research findings indicate that Current Ratio, Debt to Equity Ratio, and Earnings Per Share significantly influence the stock prices of companies in the oil, gas, and coal mining sub-sectors. Conversely, Net Profit Margin does not significantly affect the stock prices in this sector.